Carbohydrase enzyme and polyethylene glycol altered the chemical composition, growth performance and apparent nutrient digestibility of Prosopis juliflora pods meal diets fed to Boschveld chicken breed - P Tshiambara; CK Lebopa; HK Mokoboki; HS Mudau; KE Ravhuhali (Veterinary and Animal Science)
This study was designed to evaluate how treating Prosopis juliflora pods with polyethylene glycol and carbohydrase enzyme will affect its chemical composition and how the inclusion of treated P. juliflora pods in Boschveld chicken's diets will affect growth performance and nutrient digestibility. Before P. juliflora pods were administrated to the diets, they were pre-treated with enzyme, PEG and a combination of both and analysed for their nutrient content. Five diets, namely PJPM1: commercial standard pullet grower diet as a control; PJPM2: commercial standard grower diet with untreated 30 % of P. juliflora; PJPM3: commercial standard grower diet with PEG treated 30 % of P. juliflora; PJPM4: commercial standard grower diet with carbohydrase enzyme treated 30 % of P. juliflora; PJPM5: commercial standard grower diet with PEG and carbohydrase enzyme treated 30 % of P. juliflora. A total of 300 six-week-old Boschveld chickens were used in this trial. After 42 days of feeding trial, three Boschveld chickens per replicate (n = 90) were randomly selected for the determination of nutrient digestibility. Results on the chemical composition of raw P. juliflora pods meal, pre-treated with enzyme, PEG and combination of both show significant difference (P < 0.05) in CP, Ash, NDF, CF, EE, Hemicellulose, NFC and NFE. Only overall feed intake shows significant different (P < 0.05) in all dietary treatments and all the measured parameters of nutrient digestibility. Enzyme and PEG positively contribute to the chemical composition, growth performance, and nutrient digestibility of diets containing P. juliflora fed to Boschveld chickens.